Simulation of a solar funnel cooker using MATLAB - Cubero-Leiva, Rafael; Ruivo, Celestino R.; Domínguez-Muñoz, Fernando; Villatoro-Machuca, Francisco Román (My University, 2018)
A software for the calculation of the radiation heat transfer in solar funnel cookers by means of the radiosity method has been developed in Matlab. The software has been used to study a folding solar cooker. The cooker geometry is discretized using a triangular mesh where a piecewise constant approximation is assumed for the radiosity function. Form factors, including self-occlusions, are calculated by properly refining the triangular mesh. The concentration factor of the solar cooker is estimated as a function of its position and orientation with respect to that of the Sun.
Keywords: Energía solar - Investigación - Congresos; Solar cooker; Concentration factor; Numerical model; Radiation heat transfer; Radiosity method